Second Ethiopia Economic Update : Laying the Foundation for Achieving Middle Income Status - World Bank (Washington, DC, 2014)
Over the past decade, Ethiopia has achieved high economic growth, averaging 10.7 percent per year. In 2012, Ethiopia was the 12th fastest growing economy in the World. If the country can continue its historically impressive growth performance, it could potentially reach middle income status by 2025. This, in turn, may require an adjustment in economic policy to phase in the private sector as an additional engine of growth. Moreover, Ethiopia needs to make progress on two related important fronts: enhancing domestic savings, and, resolving the bottlenecks of the trade logistics system. This Second Ethiopia economic update, prepared in collaboration with the Government of Ethiopia, offers policy guidance on how to move forward. Chapter one discusses Ethiopia's growth strategy, which emphasizes a strong expansion of public investment. This model has delivered impressive results, although the underlying macro policy mix highlights important challenges going forward suggesting that an adjustment to strategy may be warranted. One policy challenge relates to raising sufficient domestic savings to finance one of the highest public investment rates in the world, as discussed in chapter two. Another challenge relates to strengthening the competitiveness of the economy, to boost the lagging export performance, and attract foreign direct investment. Ethiopia's trade logistics system is a key constraint in this regard, as highlighted in chapter three.